VD_FINDINFO Jug / 2012 / 302 vom 13. November 2012 - VD Tribunal cantonal (2012)
PRÉVOYANCE PROFESSIONNELLE, DÉCISION DE COTISATIONS, COMMANDEMENT DE PAYER | 88 LP, 50 LPP, 66 LPP, 73 al. 1 LPP, 73 al. 2 LPP, 73 al. 3 LPP, 93 al. 1 let. c LPA-VD